The Implementation of ELLLO Web-Based Application in Teaching Listening at MA Al-Ikhlas Ujung Bone - Jabu, Baso; Risman, Muhammad; Nur, Sahril (Har Press Indonesia, 2024)
This research aims to define the use of the ELLLO web-based application in teaching listening at MA Al-Ikhlas Ujung Bone. This study was a case study that would draw a description towards the phenomenon in the field. The participants were an English teacher and the students in XII grade of MA Al-Ikhlas Ujung Bone. The research instruments employed were observation and interview. The data were collected using observation techniques including observation checklist, note-taking, collected data from teachers’ documents, and interview techniques with the teacher and students. The result of the data analysis, shows that, the teacher used and took into consideration that using the media is helpful, still it needs to look forward to the supports and hindrances that can appear particularly on ELLLO that contains video, audio, material, level and quiz. The teacher faced supports and hindrances on using ELLLO in teaching listening in the class. The supports show that the media is very helpful in teaching and practicing students’ listening to improve students’ listening skill. However, the hindrance of using the media shows that the students in the learning process need to be shadowed to anticipate students’ irrelevant activity.